Hustonian Traumatography: From The Pain Of Evils To The Color Of Words - Birak, Assia; Bouderbala, Tayeb (Journal of Human Sciences, 2021)
A traumatic childhood is for some the opportunity to use his pen and sketch his pains on the page, for diluting the weight of the evils in the ocean of words. The cathartic power of writing makes it possible to sublimate the original wound and to reborn from its ashes. The birth of a literary vocation is often the fruit of a resilient process, as if creating an object of substitution, a work, in this case, clogged the gap.This article looks at the issue of writing the trauma at Nancy Huston and the implementation of some strategies of surpassing through the mirror effects of the literary text, a set of masks games and splitting to free themselves the weight of a binding past. The scriptural act, by having the trauma inscribed in the space of the literary imagination, realizes this euphoria of self-invention, of the world and of art.